Indigenous Rights, Poetry and Decarceration - McIntosh, Tracey (Human Rights and Incarceration, 2018)
Keywords: incarceration; indigenous soveriegnty; mana motuhake; māori rights; rangatiratanga

Behind the wire: Māori women and prison - McIntosh, Tracey (Women’s Studies Journal, 2017)
Keywords: colonisation; crown policy; incarceration; prison; wāhine māori

Indigenous Insider Knowledge and Prison Identity - McIntosh, Tracey; Coster, Stan (Counterfutures, 2017)
This article draws on the personal experiences and state documentation of Stan Coster (Ngāti Kahungungu) whose life has been characterised by different forms of state confinement, including over 25 years in prison serving both short and long lags. Through the use of the Official Information Act, Stan recovered state documentation on himself spanning over 40 years. Stan is not a research participant, but a full research collaborator and is engaged in all elements of this paper, so while not a writer he is both auteur and author of this piece. Stan’s story is his own and yet many of its features speak to a much broader collective experience. His prison identity and gang identity can be seen as being both informed and generated by state sponsored activity. By traversing the issues that pertain to the crisis of mass imprisonment, Māori disproportionality in the prison system, the contribution of the state to prison, and gang identity, we look at the possibilities of drawing on knowledge acquired under conditions of state constraint.
Keywords: crown policy; crown violence; identity; incarceration; marginalisation; prison

Women, incarceration and settler colonial control - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter examines settler colonial crime control and its impacts on Indigenous women. High rates of victimisation and high levels of over-policing and over-incarceration mark Indigenous people’s experience of settler colonialism. This chapter explores the historical and contemporary conditions of colonialism through a gender lens, exploring in particular the impact of prison on Indigenous women’s lives. The chapter is based on an interview with and subsequent written notes by Professor McIntosh in 2020 discussing women, incarceration and settler colonial control in the Aotearoa New Zealand setting.
Keywords: criminalisation; crown policy; crown violence; incarceration; prison; racism; wāhine māori

Marginalised: An Insider’s View of the State, State Policies in New Zealand and Gang Formation - McIntosh, Tracey; Andrae, Dominic; Coster, Stan (Critical Criminology, 2017)
Following the annexation of Aotearoa/New Zealand by the British in 1840, Māori, as the Indigenous people of that country, experienced loss of sovereignty through the imposition of and application of new and transformative policies, including the law and unfamiliar legal and social codes. This paper considers the state and the influential legacy of an imposed, Settler-state social welfare and criminal justice system on Māori. An explicit, insider narrative will highlight how suppression, disconnection and abandonment, made manifest through particular and abusive state policies, has informed and constructed the life pathway of a member of a culturally and socially-submerged population, the Mongrel Mob gang.
Keywords: child welfare; criminal justice system; crown policy; foster care; gangs; incarceration; social welfare

Māori and Prison - McIntosh, Tracey; Workman, Kim (The Palgrave Handbook of Australian and New Zealand Criminology, Crime and Justice, 2017)
Keywords: crown policy; incarceration; racism; systematic racism